2018
DOI: 10.1111/mmi.14114
|View full text |Cite
|
Sign up to set email alerts
|

A MADS‐box transcription factor regulates a central step in sporulation of the oomycete Phytophthora infestans

Abstract: MADS-box transcription factors play significant roles in eukaryotes, but have not yet been characterized in oomycetes. Here, we describe a MADS-box protein from Phytophthora infestans, which causes late blight of potato. P. infestans and most other oomycetes express a single MADS-box gene. PiMADS is not transcribed during vegetative growth, but is induced early during asexual sporulation. Its mRNA levels oscillate in response to light, which suppresses sporulation. The protein was not detected in nonsporulatin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
19
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 22 publications
(20 citation statements)
references
References 61 publications
0
19
1
Order By: Relevance
“…The MADS-box family proteins are conserved in nearly all eukaryotes and play important roles in signal transduction, responses to environmental stresses and developmental control in plants, fungi and animals. Leesutthiphonchai and Judelson (2018) showed that a MADS−box transcription factor regulates a central step in sporulation of the oomycete Phytophthora infestans (Montagne) de Bary by regulating about 3000 sporulation−associated genes. Their results demonstrated that both mRNA and protein levels of MADS−box transcription factor decline upon P. infestans spore germination.…”
Section: Discussionmentioning
confidence: 99%
“…The MADS-box family proteins are conserved in nearly all eukaryotes and play important roles in signal transduction, responses to environmental stresses and developmental control in plants, fungi and animals. Leesutthiphonchai and Judelson (2018) showed that a MADS−box transcription factor regulates a central step in sporulation of the oomycete Phytophthora infestans (Montagne) de Bary by regulating about 3000 sporulation−associated genes. Their results demonstrated that both mRNA and protein levels of MADS−box transcription factor decline upon P. infestans spore germination.…”
Section: Discussionmentioning
confidence: 99%
“…Such events would typically not be evident in a consensus genome assembly. While the frequencies of interallelic structural and transcriptional polymorphisms in Phytophthora are not well-characterized, there have been reports of hemizygous regions in several species (Dobrowolski et al, 2002;Jiang et al, 2006;Lamour et al, 2012;Martin et al, 2013;Randall et al, 2003).…”
Section: Discussionmentioning
confidence: 99%
“…Polyclonal antibodies against NR were obtained from Agrisera (catalog number AS08 310). Blotting was performed using HRP-labeled anti-rabbit IgG as described [88]. As a positive control, the Ph .…”
Section: Methodsmentioning
confidence: 99%